The Philosophical Poetics of Alfarabi Avicenna and Averroes. - Kemal, Salim (Culture and civilisation in the Middle East., 2012)
This book examines the studies of Aristotle's Poetics and its related texts in which three Medieval philosophers - Alfarabi, Avicenna and Averroes - proposed a conception of poetic validity (beauty), and a just relation between subjects in a community (goodness). The work considers the relation of the Poetics to other Aristotelian texts, the transmission of these works to the commentators' context, and the motivations driving the commentators' reception of the texts. The book focuses on issues central to the classical relation of beauty to truth and goodness.